Health system governance in settings with conflict-affected populations: a systematic review. Issue 5 (22nd March 2022) - Lokot, Michelle; Bou-Orm, Ibrahim; Zreik, Thurayya; Kik, Nour; Fuhr, Daniela C; El Masri, Rozane; Meagher, Kristen; Smith, James; Asmar, Michele Kosremelli; McKee, Martin; Roberts, Bayard
Abstract: Health system governance has been recognized as critical to strengthening healthcare responses in settings with conflict-affected populations. The aim of this review was to examine existing evidence on health system governance in settings with conflict-affected populations globally. The specific objectives were (1) to describe the characteristics of the eligible studies; (2) to describe the principles of health system governance; (3) to examine evidence on barriers and facilitators for stronger health system governance; and (4) to analyse the quality of available evidence. A systematic review methodology was used following Preferred Reporting Items for Systematic Review and Meta-Analysis criteria. We searched six academic databases and used grey literature sources. We included papers reporting empirical findings on health system governance among populations affected by armed conflict, including refugees, asylum seekers, internally displaced populations, conflict-affected non-displaced populations and post-conflict populations. Data were analysed according to the study objectives and informed primarily by a governance framework from the literature. Quality appraisal was conducted using an adapted version of the Mixed Methods Appraisal Tool. Of the 6511 papers identified through database searches, 34 studies met eligibility criteria. Few studies provided a theoretical framework or definition for governance. The most frequently identifiable governance principles related to participation and coordination, followed by equity and inclusiveness and intelligence and information. The least frequently identifiable governance principles related to rule of law, ethics and responsiveness. Across studies, the most common facilitators of governance were collaboration between stakeholders, bottom-up and community-based governance structures, inclusive policies and longer-term vision. The most common barriers related to poor coordination, mistrust, lack of a harmonized health response, lack of clarity on stakeholder responsibilities, financial support and donor influence. This review highlights the need for more theoretically informed empirical research on health system governance in settings with conflict-affected populations that draws on existing frameworks for governance.